2013
DOI: 10.1002/jcc.23357
|View full text |Cite
|
Sign up to set email alerts
|

A high-accuracy theoretical study of the CHnP Systemsn = 1-3

Abstract: We have performed high-level electronic structure computations on the most important species of the CH(n)P systems n = 1-3 to characterize them and provide reliable information about the equilibrium and vibrationally averaged molecular structures, rotational constants, vibrational frequencies (harmonic and anharmonic), formation enthalpies, and vertical excitation energies. Those chemical systems are intermediates for several important reactions and also prototypical phosphorus-carbon compounds; however, they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…[14][15][16] Phosphaethene, H-PQCH 2 has been studied more thoroughly both by theory and experiment. [15][16][17][18][19][20][21][22][23][24][25] The X 1 A 0 singlet ground state of H-PQCH 2 was found to be more stable than P-CH 3 by 1.53 eV and the barrier height for isomerization is 0.88 eV. 15 On the triplet surface, the stability order is reversed, the X 3 A 2 triplet ground state of P-CH 3 is lower in energy by 1.26 eV than the 3 A 0 state of HPQCH 2 and the corresponding barrier for a [1,2] hydrogen shift is 1.06 eV.…”
Section: A Introductionmentioning
confidence: 99%
“…[14][15][16] Phosphaethene, H-PQCH 2 has been studied more thoroughly both by theory and experiment. [15][16][17][18][19][20][21][22][23][24][25] The X 1 A 0 singlet ground state of H-PQCH 2 was found to be more stable than P-CH 3 by 1.53 eV and the barrier height for isomerization is 0.88 eV. 15 On the triplet surface, the stability order is reversed, the X 3 A 2 triplet ground state of P-CH 3 is lower in energy by 1.26 eV than the 3 A 0 state of HPQCH 2 and the corresponding barrier for a [1,2] hydrogen shift is 1.06 eV.…”
Section: A Introductionmentioning
confidence: 99%
“…Thermochemical properties (enthalpy, entropy, and heat capacity) of 40 compounds containing pentavalent P atoms were evaluated at the same level of theory using the atomization energy procedure and an explicit treatment of the hindered rotors . More recently, high accuracy theoretical calculations based on coupled cluster theory were implemented for the determination of enthalpy of formation of few phosphorus compounds, but only for species containing a limited number of heavy atoms. , Zhu and Bozzelli , used several density functional and ab initio computational methods to determine thermochemical parameters, reaction paths, and kinetic barriers for sulfur compounds. They recommended the G3MP2 and CBS-QB3 composite methods for these carbon–sulfur-oxygen system, when they can be applied.…”
Section: Introductionmentioning
confidence: 99%
“…Substituent effects (Mes*, Mes, Ph, t Bu) were also studied for the 1,3,5‐triphosphabenzene and 1,3‐isophosphinine 17. Recently, highly accurate calculations on various isomers of CH n P ( n = 1–3) systems have been reported that shed light on the simplest PC systems 18. An interesting theoretical study by Nyulaszi et al investigated the substituent effect on the stability of phosphinidene fragments in a series of isodesmic reactions 19…”
Section: Introductionmentioning
confidence: 99%